On the Number of Pairs of Points in a Quadratic Equation with Rational Distance (European Journal of Pure and Applied Mathematics, 2017)
In this paper is shown a solution to the number of pair of points in a quadratic equation with rational distance, this result have an important impact to solve the open problem "Points on a parabola" [5] proposed in The Center for Discrete Mathematics and Theoretical Computer Science (DIMACS), because it's an aproach to set down basis in the problem.